2016
DOI: 10.1002/lary.25871
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in thyroid surgery are affected by racial, economic, and healthcare system demographics

Abstract: 4. Laryngoscope, 126:2194-2199, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Another study by Sosa et al (5) revealed that the majority of Blacks had surgery by the lowest-volume surgeons, as compared with a smaller proportion of Whites. In another study, Al-Qurayshi et al analyzed more than 20,000 thyroidectomies and found that African American patients from high-risk communities (risk was based on smoking, obesity, excessive alcohol consumption, educational level, unemployment, and income among other factors) were more commonly operated on by low-volume surgeons, with postoperative complications being more common in this population (15). However, even when surgeon volume was adjusted for, Sosa et al found that significant racial disparities in length of stay and cost persisted (5).…”
Section: Disease Care Issn: 2329-9711 | November 2020 | Volume 32 | Imentioning
confidence: 99%
“…Another study by Sosa et al (5) revealed that the majority of Blacks had surgery by the lowest-volume surgeons, as compared with a smaller proportion of Whites. In another study, Al-Qurayshi et al analyzed more than 20,000 thyroidectomies and found that African American patients from high-risk communities (risk was based on smoking, obesity, excessive alcohol consumption, educational level, unemployment, and income among other factors) were more commonly operated on by low-volume surgeons, with postoperative complications being more common in this population (15). However, even when surgeon volume was adjusted for, Sosa et al found that significant racial disparities in length of stay and cost persisted (5).…”
Section: Disease Care Issn: 2329-9711 | November 2020 | Volume 32 | Imentioning
confidence: 99%
“… 37 Women and African Americans are affected disproportionately, and, unfortunately, this results in higher complication rates. 43 NSQIP (National Surgical Quality Improvement Program) data have shown that most of the patients offered outpatient thyroidectomy have private insurance. The decision to offer outpatient thyroidectomy to a patient may be due to the patient’s higher socioeconomic stratum and closer proximity to tertiary centers in urban areas.…”
Section: Factors Relating To Patient Selectionmentioning
confidence: 99%
“…15 Additional studies have shown decreases in operative times, decreased length of stay, and an increase in outpatient surgery with higher volume surgeons. [16][17][18][19] This could be one of the reasons why low-volume centers and community cancer centers favor unilateral lobectomy. Further studies are needed to explore this discrepancy.…”
Section: Thyroid Lobectomy Versus Total Thyroidectomymentioning
confidence: 99%
“…This differential could potentially lead to disparities in care as patients who are in lower socioeconomic groups and minorities have been shown previously to get care more often with lower volume surgeons. 27 This care was also more likely to be associated with poorer outcomes as lower volume surgeons have been shown to have poorer outcomes for thyroid surgery. 8…”
Section: Central Neck Dissectionmentioning
confidence: 99%